Big Eight Audit Firms, Audit Tenure and Earnings Management: Empirical Evidence from China - ZHANG, NAN (2016)
This paper examines the effect of audit reputation and various forms of audit tenure on earnings management for Chinese listed firms. Consistent with prior research (Chen et al., 2011), Big 8 audit firms in China enjoy higher reputation and are considered as of higher quality than local or regional audit firms. Also, companies audited by Big Eight audit firms tend to have less earnings management and thus higher earnings quality. On the other hand, audit tenure is rather complex as audit rotation could occur at either partner level or firm level. In order to observe their differentiated influence on earnings management, I will investigate the two forms of audit rotation separately. Using a sample of 390 China listed firms over the period from 2004 to 2014, I find evidence that Top 8 audited firms tend to have higher earnings quality compared to companies audited by local small audit firms. In addition, earnings quality improves with the audit firm tenure. However, no significant relationship is observed between audit partner tenure (rotation) and earnings management, neither at mandatory nor voluntary level.